Convivendo com o lixo: a vulnerabilidade socioambiental no Bairro Graminha – Leme/SP - Orsi, Rafael A. (2012)
Urban space occupation occurs in an extremely disordered way. Political, economical and social aspects converge to create a problem that affects mostly poor people, who are impelled to occupy areas where social and environmental problems are likely to emerge. Floods, landslides and different forms of pollution have more effects on the most vulnerable groups. In many cases, actions taken by the government legitimate this structure and reinforce its reproduction. This work seeks to confirm both that poor people are vulnerable to social and environmental problems resulting from inappropriate urban solid waste disposal and that the local government contributes to this situation. It is assumed that the issue is related first to the government‟s disregard for poor people who live in unhealthy places and second to the inability of such people to demand for better living conditions. In this study, a waste disposal area within the Jardim Graminha neighborhood in Leme (São Paulo) was selected to be analyzed by means of systematic observation. The study clearly shows that poor people living near that area where different types of garbage are disposed are vulnerable and the government does not control the situation. It is also pointed out that governmental intervention and the use of political and technical tools are necessary for planning and managing the area to mitigate these problems and to decrease poor people‟s social and environmental vulnerability.